Military Mergers: The Reintegration of Armed Forces After Civil Wars - Miller, Anja (Tufts Archival Research Center, 2005)
Volume 25, Issue 2. Summer Miller argues that the success of any peace process hinges upon the ability of the formerly warring parties to reintegrate their armed forces. The paper analyzes six military mergers and suggests guidelines for successful reintegrations.